Fatores associados aos componentes de aptidão e nível de atividade física de usuários da Estratégia de Saúde da Família, Município de Botucatu, Estado de São Paulo, Brasil, 2006 a 2007 - Michelin, Edilaine [UNESP]; Corrente, Jose Eduardo [UNESP]; Burini, Roberto Carlos [UNESP] (FapUNIFESP (SciELO), 2011)
Objective: to diagnose physical activity level and fitness, and related factors among users of the Family Health Strategy (FHS) of Rubião Junior District, Municipality of Botucatu-SP, Brazil, from 2006 to 2007. Methodology: a cross-sectional study that evaluated physical activity levels (PAL), demographic, socioeconomic, and health conditions (PAL-IPAQ-8), body composition [Body Mass Index (BMI), and waist circumference (WC)], trunk flexibility (FLEX), and handgrip strength (HGS) of 394 FHS studied users (aged 35-85 years). Results: there was a low and high PAL in, respectively, 17.0% and 36.3% of the sample with greater unfitness for flexibility (77.2%) than HGS (48.4%); after adjustment of the regression model, individuals with fair/poor health had 60.0% less likely to show high PAL, and women and individuals with altered WC showed, respectively, 90.0% and 60.0% less chance of being unfit for HGS; individuals with education level until elementary school and poor health perception showed, respectively, 3.2 and 2.7 times more likely to have bad HGS. Conclusion: the knowledge of FHS’s activity and physical fitness profile may contribute to health diagnosis of their users.

Objetivo: diagnosticar o nível de atividade, aptidão física e fatores associados entre usuários da Estratégia Saúde da Família (ESF) do distrito de Rubião Jr., município de Botucatu-SP, Brasil, entre 2006 e 2007. Metodologia: estudo transversal que avaliou níveis de atividade física (NAF), informações demográficas, socioeconômicas e estado de saúde (NAF-IPAQ 8), composição corporal [índice de massa corporal (IMC) e circunferência abdominal (CA)], flexibilidade de tronco (FLEX) e força de preensão manual (FPM) entre os 394 usuários da ESF (35-85 anos de idade) estudados. Resultados: observou-se baixo e alto NAF em, respectivamente, 17,0% e 36,3% da amostra, com maior inaptidão para flexibilidade (77,2%) do que para FPM (48,4%); no modelo de regressão logística ajustado, indivíduos com estado de saúde regular/ruim apresentaram 60,0% menos chance de terem NAF alto, e mulheres e indivíduos com CA alterada tiveram, respectivamente, 90,0% e 60,0% menos chances de inaptidão para FPM; indivíduos com escolaridade até o ensino fundamental e má percepção de saúde tiveram, respectivamente, 3,2 e 2,7 vezes mais chance de terem FPM ruim. Conclusão: o conhecimento do perfil de atividade e aptidão física nas ESF pode contribuir para o diagnóstico de saúde de seus usuários.
Factors Associated with the Components of Fitness and Physical Activity Level in Users of Family Health Strategy, Municipality of Botucatu, state of São Paulo, Brazil, 2006 to 2007
Keywords: Motor activity; Physical fitness; Questionnaires; Primary health care; Cross-sectional studies.; Atividade motora; Aptidão física; Questionários; Atenção primária à saúde; Estudos transversais